Elementos Arquiteturais do Substrato da Lagoa dos Patos Revelados por Sísmica de Alta Resolução - Weschenfelder, Jair (2006)
A high-resolution seismic survey was performed on the Lagoa dos Patos, southern Brazil. The survey was conducted aboard the research vessel LARUS of the Fundação Universidade Federal do Rio Grande. The seismic profiles were obtained using a 3.5 kilohertz frequency, which provided a rather good penetration depth and resolution of the records. Results of the seismic records allowed the determination and mapping of seismic facies and seismic sequences, as well as related architectural elements, which were identified basically through the configuration patterns of the seismic reflectors. The analysis of the seismic records allowed the identification of the architectural elements that build up the sedimentary pile accumulated in the coastal prism of the State of Rio Grande do Sul, contributing to a better understanding of the geological evolution of the southern Brazilian coastal plain during the Quaternary period.